POSITIONING INSTALLATION FOR ANCHORAGES IN THE PREFABRICATION OF PANELS OF REINFORCED CEMENT MORTAR - FRADERA PELLICER, CARLOS (2012)
Anchor positioning equipment for pre-fabricating panels of reinforced cement mortar (10) that includes a prestressed biaxial reinforcement (9). The panel has some versatile actuator means (6) embedded into the mass of cement mortar (10), that do not project from any of the faces (11) thereof, for handling and/or securing said panel to the structure of a building. The means (6) comprise, on the one hand, means for retaining (13) in the set mortar mass and, panel anchoring means (14). The equipment has a fixed base structure (2) for supporting stable seat elastic arrangements (5), which receive means (6) and, on the other hand, movable frameworks (1) comprising gripping arrangements (3) for gripping means (6). Movable frameworks (1) are responsible for removing means (6) from stable seat elastic arrangements (5).